One‐Step Fabrication of CdS/Ag2S Heterojunction Composites and Its Enhanced Visible‐Light Photocatalytic Degradation Performance. Issue 7 (28th March 2022) - Wang, Shuang; Yu, Minghui; Yu, Hao; Cheng, Yuye; Dou, Minghao; Gong, Xiaoyu; Li, Zhiqiang; Shao, Hongyu; Chen, Guangyu; Li, Shenjie; Chen, Yanyan
Abstract: The design and construction of Ag2 S heterostructures capable of significantly separating photocarriers is a significant challenge in photocatalysis. In this study, CdS/Ag2 S heterojunction composite photocatalyst is fabricated through a simple one‐step hydrothermal method. The composite structure is characterized by X‐ray diffraction, transmission electron microscopy, scanning electron microscopy, X‐ray photoelectron spectroscopy, and UV‐visible diffuse reflection spectroscopy. Under visible light irradiation, the photocatalytic activity of the sample is evaluated by degradation of methyl orange. The photoelectric chemical performance of the CdS nanoparticles modified by Ag2 S is closely related to the ratio of Cd/Ag cation. The experimental results show that the sample ACS‐2 (CdS‐Ag2 S = 1:1) composite has higher charge transfer/separation efficiency and longer carrier life. The degradation efficiency reaches 74.4% within 30 min, and the degradation rate constant is 0.047 min −1 . After four cycles, the degradation efficiency of the catalyst only decreases slightly, indicating that the CdS/Ag2 S catalyst has good stability and repeatability. Meanwhile, the study of the photocatalytic mechanism shows that O 1 − is the primary active substance in the catalytic process, and h + and OH play a secondary role. This work provides a great significance for constructing efficient Ag2 S‐based heterojunction photocatalyst systems. Abstract : This paper presents a simple solution‐based scheme for the one‐pot synthesis of highly efficient photocatalysts composed of Ag2 S/CdS with heterojunction. The active site provided by Ag2 S greatly improves degradation of methyl orange under visible‐light radiation, which provides an idea for the simple preparation of efficient photocatalysts.